2003
DOI: 10.1021/jf020978a
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Dependent Phytotoxicity of Catechins and Other Flavonoids:  Flavonoid Conversions by Cell-free Protein Extracts of Centaurea maculosa (Spotted Knapweed) Roots

Abstract: Invasive plants are believed to succeed in part by secretion of allelochemicals, thus displacing competing plant species. Centaurea maculosa (spotted knapweed) provides a classic example of this process. We have previously reported that spotted knapweed roots secrete (+/-)-catechin and that (-)-catechin, but not (+)-catechin, is phytotoxic and hence may be a major contributor to C. maculosa's invasive behavior in the rhizosphere. In this communication, we explore both structure/activity relationships for flavo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
2
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 28 publications
2
41
2
1
Order By: Relevance
“…First, the phytotoxicity is highly species-dependent. For instance ( )-catechin had no significant effect on germination and root elongation of six weed species (Bais et al, 2003) but reduced by half the root elongation of lettuce at 32 ppm (Iqbal et al, 2003). Second the dynamic of the allelochemicals is poorly understood.…”
Section: Allelopathic Compounds Released During Decompositionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the phytotoxicity is highly species-dependent. For instance ( )-catechin had no significant effect on germination and root elongation of six weed species (Bais et al, 2003) but reduced by half the root elongation of lettuce at 32 ppm (Iqbal et al, 2003). Second the dynamic of the allelochemicals is poorly understood.…”
Section: Allelopathic Compounds Released During Decompositionmentioning
confidence: 99%
“…eral weed species (Bais et al, 2003) but at a high dose, it exhibited a phytotoxic effect on lettuce (Golisz et al, 2007). These molecules may mediate the allelopathic activity of buckwheat.…”
Section: Allelopathymentioning
confidence: 99%
“…Likewise, the ANR protein from grape also produced (+)-E (Gargouri et al, 2009, and the two CsANRs exhibit higher amino acid sequence identity to VvANR (79% and 83%) than to MtANR or AtANR (64%-73%). In contrast to the widely distributed and well-documented (+)-catechin and (2)-E isomers, there are only a few reports of the presence of (2)-catechin and (+)-E in plants, such as (2)-catechin from Chamaebatia foliolosa and Centaurea maculosa (Nahrstedt et al, 1987;Bais et al, 2003;Perry et al, 2005) and (+)-E from Palmae spp. and Paullinia cupana (Delle Monache et al, 1972;Yamaguti-Sasaki et al, 2007).…”
Section: Tea Anrs and Pa Engineering In Transgenic Plantsmentioning
confidence: 99%
“…Furthermore, when Blair et al 16,17 developed more reliable techniques, they found catechin levels from liquid media to be two orders of magnitude lower than previously reported and three orders of magnitude lower, if found at all, from field sites infested with C. stoebe. Later, Lau et al 25 reported that using activated carbon can cause experimental artifacts, either decreasing or increasing growth of plants. Such findings led Blair et al [16][17][18] to call into question the role of catechin as an ecologically important allelochemical of C. stoebe.…”
Section: Proving Allelopathymentioning
confidence: 99%